(3GdSjGSGJ GdeUQajI, JMdjd GdbhGFe GdeGdjI hbjGS GGdaYGdjI, GdLhGfH GdJfXejI hGdEOGQIs - (3YHO GdZaGQ(B, (3Mfajs; (3YHO GdSdGe CHh bMa(B, s ((3GdEScfOQjI(B:s (3GdecJH GdYQHj GdMOjK(B,s, 2000)
(3GdfXGe GdeUQaj aj eUQ hJWhQg, SjGSGJ GdSjhdI hGdhOGFY, GdbQhV hGdSdajGJ, JMdjd GdbhGFe GdeGdjI ddHfhc GdJLGQjI, JNUjU GdCehGd Ydi HfhO GdJhXja ddHfc GdJLGQjs
Keywords: (3GdEOGQI GdeGdjIs; (3GdHfhcs